Forming self-evaluation of learning achievements as a pedagogical problem - Бахмат, Людмила Володимирівна (Scientific notes of the pedagogical department, 2015)
The article deals with the issues of forming learning achievements self-evaluation in the context of organizing professional training of future teachers. The main focus is permanent control of learning achievements quality that can in a complex characterize the real state of professional training of a future teacher.